Breastfeeding and the nutritional transition in the Latin American and Caribbean Region: a success story? Amamentação e transição nutricional na América Latina e Caribe: um caso bem-sucedido? - Rafael Pérez-Escamilla (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2003)
The objectives of this paper are to examine recent breastfeeding duration trends in Latin America and the Caribbean to document: (a) rural-urban differentials, (b) differences in educational levels, and (c) changes in breastfeeding duration across time. Secondary data analyses were conducted with 23 Demographic and Health Surveys collected between the mid-1980s and mid-1990s. Results indicate that median breastfeeding duration is still greater in rural (as compared to urban) areas and among less (versus more) educated women, although these differentials are decreasing with time. In five of the six countries examined for secular trends, breastfeeding duration continues to increase in both rural and urban areas. Breastfeeding duration in urban and rural areas was strongly correlated within countries. Breastfeeding duration improved more among women with the highest and declined among those with the lowest levels of education. Results indicate that breastfeeding duration has increased in Latin America and the Caribbean at a time when the opposite was predicted, given the region's increased urbanization. Breastfeeding protection policies and promotion programs may explain part of the increase in breastfeeding duration. Os objetivos deste artigo incluem examinar tendências recentes na duração da amamentação na América Latina e Caribe e documentar: (a) diferenciais entre áreas rurais e urbanas, (b) diferenças em escolaridade materna e (c) mudanças na duração do aleitamento materno ao longo do tempo. Foram realizadas análises de dados secundários a partir de 23 pesquisas demográficas em saúde conduzidas entre meados das décadas de 80 e 90. Os resultados indicam que a duração mediana da amamentação continua sendo maior nas áreas rurais comparadas com as urbanas e entre mulheres com menos escolaridade, embora tais diferenças estejam diminuindo ao longo do tempo. Em cinco dos seis países estudados em relação a tendências seculares, continua aumentando a duração da amamentação, tanto em áreas rurais quanto urbanas. A duração da amamentação em áreas urbanas e rurais estava fortemente correlacionada dentro dos países. A duração do aleitamento aumentou mais entre mulheres com maior escolaridade e declinou entre mulheres com menor escolaridade. Os resultados indicam que a duração do aleitamento vem aumentando na América Latina e Caribe numa época em que era previsto o oposto, em vista da crescente urbanização da região. Políticas de proteção ao aleitamento materno e programas de promoção podem explicar parte do aumento na duração do aleitamento materno.